Compound specific isotope analysis of hexachlorocyclohexane isomers: a method for source fingerprinting and field investigation of in situ biodegradation. (6th February 2015) - Chartrand, Michelle; Passeport, Elodie; Rose, Carla; Lacrampe‐Couloume, Georges; Bidleman, Terry F.; Jantunen, Liisa M.; Sherwood Lollar, Barbara
Abstract : RATIONALE: The manufacturing and uses of hexachlorocyclohexane (HCH) have resulted in a serious environmental challenge and legacy. This study highlights the ability of compound specific isotope analysis (CSIA) to distinguish among various HCH sources and to support the evaluation of the potential for in situ biodegradation in contaminated groundwater. METHODS: Tests were conducted to verify the absence of significant isotope fractionation during HCH sample pre‐concentration including dichloromethane extraction, solvent exchange into iso‐octane, and H2 SO4 clean‐up, and analysis by gas chromatography/combustion‐isotope ratio mass spectrometry (GC/C‐IRMS). The method was then applied to four Technical Grade (TG) HCH mixtures procured from different sources and to groundwater samples from a contaminated site. RESULTS: The pre‐concentration method enabled determination of carbon isotope ratios (δ 13 C values) of HCH isomers with no significant isotopic fractionation. The TG‐HCH mixtures had significantly different δ 13 C values. Moreover, for any given TG‐HCH, all isomers had δ 13 C values within 1.1‰ of each other – a distinctly uniform fingerprint. At the HCH‐contaminated field site, compared with source wells, downgradient wells showed significant (up to 5.1‰) enrichment in 13 C and the δ 13 C values of the HCH isomers were significantly different from each other. CONCLUSIONS: A method was successfully developed for the CSIA of HCH isomers that showed potential for HCH source differentiation and identification of HCH in situ biodegradation. At the HCH‐contaminated site, the observed preferential isotopic enrichment of certain isomers relative to others for a given source allows differentiation between biodegraded and non‐biodegraded HCH. Copyright © 2015 John Wiley & Sons, Ltd.